2016
DOI: 10.1155/2016/3121538
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Saving Management Mechanism Based on Hybrid Energy Supplies for LTE Heterogeneous Networks

Abstract: Aiming at the lack of integrated energy-saving (ES) methods based on hybrid energy supplies in LTE heterogeneous networks, a novel ES management mechanism considering hybrid energy supplies and self-organized network (SON) is proposed. The mechanism firstly constructs ES optimization model with hybrid energy supplies. And then a SON framework is proposed to resolve the model under practical networks. According to the framework, we divide the ES problem into four stages, which are traffic variation prediction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Mobile devices connect to the cloud hub over a wireless network and send their own tasks to the cloud hub. ere is no need to perform data management calculations or other processing [12], just provide data input and output in the cloud center. is 2 Mobile Information Systems feature allows users to download and install applications, store mobile storage memory, view data on a variety of devices and platforms, improve application compatibility, and cover mobile devices [13,14].…”
Section: Edge Server Deployment Algorithm Design Experimentsmentioning
confidence: 99%
“…Mobile devices connect to the cloud hub over a wireless network and send their own tasks to the cloud hub. ere is no need to perform data management calculations or other processing [12], just provide data input and output in the cloud center. is 2 Mobile Information Systems feature allows users to download and install applications, store mobile storage memory, view data on a variety of devices and platforms, improve application compatibility, and cover mobile devices [13,14].…”
Section: Edge Server Deployment Algorithm Design Experimentsmentioning
confidence: 99%
“…where the denominator provides the maximum achievable data rate and b τ is the bandwidth of a RB in the network, which is 180 kHz in LTE [10]. By obtaining P τ j and τ * ij from (2) and (3) respectively, we can calculate the minimum amount of power in W that has to be allocated by BS j to UE i as…”
Section: Density- Energy-and Spectrum-aware Base Station Schedulmentioning
confidence: 99%
“…That is why P 0 is considered in the problem formulations. Generally, P 0 is around 500 W and 15 W for macro and small cells, respectively [10]. This model can be expanded by including switching power consumption which is out of scope of this work [12], [13].…”
Section: Density- Energy-and Spectrum-aware Base Station Schedulmentioning
confidence: 99%
“…It has been reported that the telecommunication industry is responsible for about 2 percent of the total CO 2 emissions worldwide, and the percentage is expected to double in 2020 [8]. To reduce the carbon footprint, recently, integrating some green energy, such as wind and solar power, into the existing cellular networks has became another research priority [9][10][11][12]. German mobile operator E-Plus (available: https:// nsn.com/news-events/publications/unite-magazine-issue-10/ e-plus-launches-germany-s-first-zero-co2-off-grid-base-station) has launched the first generation of green BSs by adopting a combination of solar and wind power only.…”
Section: Introductionmentioning
confidence: 99%